Design and implementation of an RSVP-based quality of service architecture for an integrated services Internet - Barzilai, T.P.; Kandlur, D.D.; Mehra, A.; Saha, D. (IEEE journal on selected areas in communications, 1998)
The Internet Engineering Task Force (IETF) is currently in the process of overhauling the architecture of the Internet to meet new challenges and support new applications. One of the most important components of that venture is the enhancement of the Internet service model from a classless best effort service architecture to an integrated services architecture supporting a multitude of classes and types of services. This paper presents the design, implementation, and experiences with a protocol architecture for the integrated services Internet. It is based on the emerging standards for resource reservation in the Internet, namely, the RSVP protocol and the associated service specifications defined by the IETF. Our architecture represents a major functional enhancement to the traditional TCP/IP protocol stack. It is scalable in terms of performance and number of network sessions, and supports a wide variety of network interfaces ranging from legacy LAN interfaces, such as Token Ring and Ethernet, to high-speed ATM interfaces. The paper also describes the implementation of this architecture on the IBM AIX platform and our experiences with the system. We then present a performance analysis of the system which quantifies the overheads imposed by all components of the QoS support, such as traffic policing, traffic shaping, and buffer management.